Self-Active Relaxation Therapy (SART) and Self-Regulation: A Comprehensive Review and Comparison of the Japanese Body Movement Approach - Kabir, Russell S.; Haramaki, Yutaka; Ki, Hyeyoung; Ohno, Hiroyuki (Frontiers in Human Neuroscience, 2018)
Relaxation programs are known for their versatility, cost-effectiveness, and ability to help people obtain skills to regulate their mental states and promote and maintain health. Self-Active Relaxation Therapy (SART) is a body-oriented approach to psychological rehabilitation that grew out of the suite of movement tasks developed in the Japanese psychotherapy known as Dohsa-hou, or the body movement method. The program for SART is designed to stretch, twist, and release areas of the upper, lower, and whole body through a set of movements which are guided by the practitioner and performed “self-actively” by the client to empower them to learn to recognize points of tension in the body and act on their own to achieve a relaxed state. Numerous studies have showed that SART is associated with reduced negative mood states and enhanced body awareness. A short version of SART has been investigated as a psychological support salon activity for the elderly, mothers raising children, special needs students, and children adapting to school. The full program has also been applied in clinical settings to address or supplement treatments for psychological and developmental conditions, and longitudinally employed in community contexts to assist residents facing long-term disaster recovery circumstances in Japan. This paper reviews the research and applications of SART as a bodymind approach by critically examining evidence and research gaps for future studies, comparing it with techniques established in the literature, and positing a self-regulatory framework for SART as a tool to become aware of bodily states, regulate mood, and manage stress through the deliberate practice of relaxation.